The Meaning Of Family Conflict In Perayaan Mati Rasa Film: A Roland Barthes Semiotic Analysis - Tariq Yazid; Desfina Citra (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the meaning of family conflict in the film "Perayaan Mati Rasa," directed by Umay Shahab, using Roland Barthes's semiotic approach. Family conflict is not merely an interpersonal event but also a cultural construct shaped by social values ​​and power relations within the family structure. As a form of mass media, film plays a crucial role in representing and constructing social reality through visual and verbal signs. This study employed qualitative methods with semiotic analysis at three levels of meaning: denotation, connotation, and myth. The data consisted of nine selected scenes categorized into three family conflict orientations: lose-lose, win-lose, and win-win. The findings indicate that the lose-lose orientation represents emotional avoidance and suppression, the win-lose orientation highlights dominance and unequal power relations between siblings, while the win-win orientation depicts reconciliation through empathy and open communication. At the myth level, the film both constructs and critiques cultural beliefs regarding the authority of the firstborn, masculinity, and ideal family harmony. Overall, the Mati Rasa Celebration portrays family conflict as a complex emotional process and emphasizes the importance of open communication in achieving constructive conflict resolution.